Cold Case Files: The Athenian Grain Merchants 386 B.C. - Wayne R. Dunham (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
While most economic analysis of the effects of market power has focused on monopoly power (a single seller of a good) or cartels among sellers, there has always remained some degree of interest in monopsony power (a single buyer) or buying cartels. In the United States there have been antitrust cases involving monopsony and buyer's cartels at least as far back as 1925, and there is continuing interest in the potential for monopsony power in the retail and health care sectors. This paper examines one of the earliest known antitrust or competition policy cases for possible lessons concerning antitrust treatment of monopsony power in the present day. In 388 B.C., grain regulators in Athens, Greece, were attempting to respond to a sharp increase in grain prices. They encouraged grain importers to form a buyers' cartel with the purpose of decreasing the price of imported grain. However, this action resulted in an overall increase in price and the grain merchants soon found themselves on trial for their lives. In this paper the information presented at that trial is used to evaluate the grain merchants' actions and the impact of monopsony on prices and consumption more generally.
Keywords: 330